Pembuatan Animasi Pendaftaran Siswa Baru Pada SMAN 5 Kepahiang Berbasis Multimedia Linier - Hidayah, Agung Kharisma; Sarwanto, Legi; Handayani, Sri (Jurnal Media Infotama, 2019)
State Senior High School 5 Kepahiang is one of the schools in Kepahiang Regency. Therefore, State Senior High School 5 Kepahiang School is a suitable choice for parents who want to send their children to high school level, especially in the Bermani Ilir, Kepahiang area, the service in providing information is not optimal because many prospective students want to get information and registration procedures to become new students. At State Senior High School 5 Kepahiang, the existing registration information is not fully understood by prospective new students. For this reason, the author created a registration for prospective new students based on linear multimedia as additional media and support for publishing information about registration tutorials for all prospective students. This animation was made using Blender software and the Adobe Premiere Pro software application. The file format resulting from the process of making this animation is MP4 format. The type of content displayed in making this animation is video, sound and text which explains the tutorial for registering new students at State Senior High School 5 Kepahiang. Testing the animated video using a questionnaire obtained an average answer of 82.8%.